2019
DOI: 10.1002/gps.5052
|View full text |Cite
|
Sign up to set email alerts
|

Finding fault: Criticism as a care management strategy and its impact on outcomes for dementia caregivers

Abstract: Background Despite a large literature on the stress process, little attention has focused on how caregivers for persons living with dementia (PLWDs) provide care and how this may impact care outcomes. Criticism is a management strategy caregivers may use to respond to behavioral symptoms. We consider whether criticism is associated with caregivers' mental health and service utilization. Methods Data are drawn from the Advancing Caregiver Training intervention study including 256 informal caregivers living with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…In a study of 256 informal caregivers living with an individual with dementia, Leggett and colleagues found that 15% used harsh communications as a management strategy. Furthermore, greater use of harsh communications was associated with significantly more caregiver burden (β=.26, p<.001) and frustration with caregiving (β=.66, p<.001), but not depressive symptoms or a desire to institutionalize the person living with dementia (Leggett, Kales, & Gitlin, 2018). In addition, the use of these forms of communication by caregivers was associated with significantly greater utilization of home services (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study of 256 informal caregivers living with an individual with dementia, Leggett and colleagues found that 15% used harsh communications as a management strategy. Furthermore, greater use of harsh communications was associated with significantly more caregiver burden (β=.26, p<.001) and frustration with caregiving (β=.66, p<.001), but not depressive symptoms or a desire to institutionalize the person living with dementia (Leggett, Kales, & Gitlin, 2018). In addition, the use of these forms of communication by caregivers was associated with significantly greater utilization of home services (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…adult day care, support groups, cleaning; β=.15, p<.05), but not health care services (i.e. use of hospital, rehabilitation facilities, physician visit, etc) (Leggett et al, 2018). Unfortunately, little research has examined the relationship between the use of negative or harsh communications and characteristics of persons with dementia and their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia is a major health concern faced by older adults (Kim & Kim, ). When diagnosed with dementia, family caregivers experience depression (Choi, Budhathoki, & Gitlin, ), stress (Leggett, Kales, & Gitlin, ), burdens (Jo & Kim, ), grief (Lee, ), as well as severe psychological pain and various life‐related challenges (Vliet, Vugt, Bakker, Koopmans, & Verhey, ). Thus, there is a need for more proactive interventions that support family caregivers of individuals with early stage dementia (Sung, Kim, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased prevalence of PWD has resulted in a need for coping and preparedness in families, and this has social implications that extend beyond personal and family concerns (National Academies of Sciences, Engineering, and Medicine, 2016). Research on family caregivers of PWD is steadily increasing, and caregivers have been shown to experience stress, depression, anxiety, and decreased self-efficacy and well-being (Choi et al, 2019;Leggett et al, 2018;Park & Park, 2015). Further, several studies have examined the maladaptive consequences between family member conflicts and economic burdens (Miranda-Castillo, Woods, & Orrell, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation